2020
DOI: 10.1177/2040622320949068
|View full text |Cite
|
Sign up to set email alerts
|

Optimal antithrombotic therapy after transcatheter aortic valve replacement in patients with atrial fibrillation

Abstract: Atrial fibrillation (AF) is prevalent in patients with aortic stenosis (AS) undergoing transcatheter aortic valve replacement (TAVR). Depending on the timing of AF detection, it is usually categorized as pre-existing AF or new-onset AF. Antiplatelet therapy, rather than a vitamin K antagonist, may be considered as the primary treatment for patients without an indication for oral anticoagulants who undergo TAVR. However, the optimal postprocedural antithrombotic regimen for patients with AF undergoing TAVR rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In terms of specific anticoagulant treatment, there is a lack of established consistency in clinical studies. Some studies recommend the use of a combination of an oral anticoagulant like warfarin and an antiplatelet drug such as aspirin or clopidogrel [26,60] . However, other studies have shown oral anticoagulant monotherapy to be safe with a lower risk of major bleeding complications than a combined therapy of an oral anticoagulant and an antiplatelet drug [61] .…”
Section: Tavrmentioning
confidence: 99%
“…In terms of specific anticoagulant treatment, there is a lack of established consistency in clinical studies. Some studies recommend the use of a combination of an oral anticoagulant like warfarin and an antiplatelet drug such as aspirin or clopidogrel [26,60] . However, other studies have shown oral anticoagulant monotherapy to be safe with a lower risk of major bleeding complications than a combined therapy of an oral anticoagulant and an antiplatelet drug [61] .…”
Section: Tavrmentioning
confidence: 99%